A construção histórica dos sistemas de numeração como recurso didático para o Ensino Fundamental I - Leite, Claudécio Gonçalves (2014)
Using the history of number systems is to create different moments for the student to experience experiences in the construction of numbers and that these will come to understand that the system used today by many cultures is a creation of all mankind. The work will speak on the topic numbering systems, using existing publications on that subject, making thus a wide bibliographic in textbooks, technical books on the subject and also results of external evaluations provided by official bodies. The objectives turn to one of the history of mathematics, as a source of understanding of the decimal numbering system, using the historical line of building other number systems so that students can compare these number systems with the system decimal and thus better understand our numbers. We believe that a view of mathematics as a ready science, which should only be "served" in the classroom, we have no more space in the classes of a society undergoing rapid and profound changes.